Development and Validation of the Scientific Reasoning Scale. (12th October 2015) - Drummond, Caitlin; Fischhoff, Baruch
Abstract: Scientific findings and innovations play an important role in a range of decisions faced by nonscientists, yet little is known about the skills that nonscientists need in order to read and evaluate scientific evidence. Drawing on research in public understanding of science, cognitive developmental psychology, and behavioral decision research, we develop an individual difference measure of scientific reasoning skills, defined as the skills needed to evaluate scientific findings in terms of the factors that determine their quality. We present the results of three studies assessing its psychometric validity. Our results indicate that the Scientific Reasoning Scale (SRS) is internally consistent and distinct from extant measures of scientific literacy. Participants with higher SRS scores are more likely to have beliefs consistent with the scientific consensus on potentially contentious issues, above and beyond education, political and religious beliefs, and scores on two widely used measures of scientific literacy. Participants with higher SRS scores also had better performance on a task requiring them to analyze scientific information. Our results suggest that the SRS provides a theoretically informed contribution to decoding lay responses to scientific results and controversies. Copyright © 2015 John Wiley & Sons, Ltd.